Comparative Analysis of Barriers and Challenges in Adoption of Electronic Health Record System in Government and Private Hospitals of Islamabad: Analysis of Barriers and challenges in Adoption of Electronic Health Record System - Jawwad , Ghazala; Asim, Maleha; Ali, Amanat; Khan , Humaira Fayyaz; Anjum, Aiman Farogh; Arain, Abdul Qudoos (Journal of Rawalpindi Medical College, 2024)
Objective: The purpose of this study was to identify the barriers and challenges in adoption of the EHR system in hospitals of Islamabad and to compare the barriers and challenges faced in adopting and running of electronic health record system in government and private hospitals of Islamabad. Materials and Methods: This multicentric cross-sectional study was carried out among 160 health providers of four government and four private hospitals in Islamabad from June 2022 to November 2022. A structured questionnaire was distributed to the management, health professionals and the staff using EHR system by simple random sampling. Data were analyzed using SPSS version 26. Independent sample t test was applied for comparative analysis of challenges and barriers in government and private hospitals. Results: The response rate for the electronic health record system survey was 160 (76%). Of those responding, 85.75% and 72% reported use of EHR system regarding patient care from government and private hospitals respectively. Around 42.5% and 83.75% government and private hospitals have fully functional EHR system and 72% from government and 90% responses from private reported use of computers as a major mode of patients’ data entry. Significant difference was found between government and private hospitals regarding social and legal barrier and lack of knowledge of EHR system (p value <0.05). Implementation of single module and multi module was a big challenge for government and private hospital respectively (p value <0.05). Conclusion: Government and private hospitals equally face the challenges and barriers tin implementation of EHR system with some barriers and challenges more prevalent in private hospitals and some in government hospitals.